Analisis Kadar Kalsium yang Diambil dengan Waktu Pemasangan Tourniquet Selama 1 Menit dan 3 Menit - Rosnita Sebayang; Muhammad Anjas Andreansyah; Agnes Felicia Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the total calcium level in serum taken with a tourniquet installation time of 1 minute and 3 minutes using an autoanalyzer. This research method is a pre-experiment with static group comparison. The average result of total calcium levels in serum with a tourniquet installation time of 1 minute is 9.40 mg/dL. In contrast, the average effect of total calcium levels in serum with a tourniquet installation time of 3 minutes is 9.55 mg/dL. In conclusion, there was no significant difference in the results of the examination of total calcium levels in serum with the duration of the tourniquet installation for 1 minute and 3 minutes. Keywords: Autoanalyzer, Calcium, Long Retention, Tourniquet